2017
DOI: 10.1186/s13195-017-0269-3
|View full text |Cite
|
Sign up to set email alerts
|

Digitally translated Self-Administered Gerocognitive Examination (eSAGE): relationship with its validated paper version, neuropsychological evaluations, and clinical assessments

Abstract: BackgroundThe original paper Self-Administered Gerocognitive Examination (SAGE) is a valid and reliable cognitive assessment tool used to identify individuals with mild cognitive impairment (MCI) or early dementia. We evaluated identical test questions in a digital format (eSAGE) made for tablet use with the goals of calibrating it against SAGE and establishing its association with other neuropsychological tests and clinical assessments of cognitive impairment.MethodsSubjects aged 50 and over who had taken SAG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 74 publications
3
57
0
1
Order By: Relevance
“…Both tests were excellent at discriminating dementia patients from SCI patients with a sensitivity of 1 for both GSCT and MoCA while showing a specificity of 0.9 and 0.56, respectively. This result is similar to the differential capabilities of other digital cognitive test showing sensitivity and specificity scores ranging from 0.85-1 and 0.81-1 respectively (31)(32)(33). Both tests also showed similar capabilities when discriminating between SCI and MCI patients with AUC scores of 0.74.…”
Section: Discussionsupporting
confidence: 84%
“…Both tests were excellent at discriminating dementia patients from SCI patients with a sensitivity of 1 for both GSCT and MoCA while showing a specificity of 0.9 and 0.56, respectively. This result is similar to the differential capabilities of other digital cognitive test showing sensitivity and specificity scores ranging from 0.85-1 and 0.81-1 respectively (31)(32)(33). Both tests also showed similar capabilities when discriminating between SCI and MCI patients with AUC scores of 0.74.…”
Section: Discussionsupporting
confidence: 84%
“…Most questions were scored by the eSAGE software, but trained assessors scored drawings. Results showed that the eSAGE was highly correlated with the validated SAGE and other neuropsychological tests (Scharre et al, 2017).…”
Section: Resultsmentioning
confidence: 96%
“…Six articles described translating paper-based or personal computer (PC)-based neuropsychological tests to mobile platforms. Five articles focused on converting paper-based tests (Berg et al, 2018; Ruggeri et al, 2016; Scharre et al, 2017; Wu et al, 2015, 2017) and one investigated converting a PC-based test (Mielke et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations